Experimental investigation of microheat pipes for high‐power light‐emitting diode modules. (1st October 2013) - Luo, Yi; Liu, Gang; Zou, Liangliang; Yang, Yanxia; Wang, Xiaodong
Abstract : A light‐emitting diode (LED) is a novel electronic light source that provides a direct conversion of electrical energy into light. A typical LED power package has a heat flux of 100 W/cm 2, thus high power LEDs face severe thermal challenges because of their small size and general lack of a proper thermal path. The advantage of microheat pipes (MHPs) which are largely used in heat dissipation of microdevices is based on phase change. With the trend of using a silicon wafer as the substrate in LED manufacturing, a silicon‐glass MHP was fabricated for the quick spread of heat from the LEDs. Flat plate grooved MHPs are introduced. The grooves were fabricated on the silicon wafer and followed by bonding with Pyrex 7740 glass. Water was selected as the working liquid and the charge rate was 40%. The temperature test experiments were carried out to test the feasibility of the MHPs in LED heat conduction, and the preliminary experimental results indicate that the heat conductivity of MHPs without a vapour chamber is better than that of MHPs with a vapour chamber, which is even better than that of the silicon wafer.